(3)/(x-4)=1

Simple and best practice solution for (3)/(x-4)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3)/(x-4)=1 equation:



(3)/(x-4)=1
We move all terms to the left:
(3)/(x-4)-(1)=0
Domain of the equation: (x-4)!=0
We move all terms containing x to the left, all other terms to the right
x!=4
x∈R
We multiply all the terms by the denominator
-1*(x-4)+3=0
We move all terms containing x to the left, all other terms to the right
-1*(x-4)=-3

See similar equations:

| 4p/3=12/1 | | (5÷x)+1=(4÷3) | | 15428x-16=-16 | | d+1/3=4 | | 8x+17+6x-7+3x-29=180 | | 2x+8=6+6x | | 24=2n+10 | | 4a-2=19 | | 80=16*v | | X³+y³=8 | | √9/64x=4 | | X3+y3=8 | | 2+(x+4)=(2+x)+4 | | n÷8-4=-7 | | 2x+3+3x-1=52 | | -3(-2b-1)=21 | | (5/4)x+7=13+x | | 2m-44=76-8mm= | | 25=4n-3n= | | 2a+2a+4=20 | | h(3)=2^3 | | 5+4n=13n= | | (10+2x)/3=4x= | | 2x=15x= | | 2+x=7x-15 | | 6x-+2=4x+10 | | 11*x+35=15*x | | 11+3m*6=42m-13 | | 100=3^x | | 18/x=x/50 | | 2(x+4)=(x+4)2 | | 10h/20=0.5 |

Equations solver categories